PEMBERDAYAAN KELOMPOK TANI HUTAN (KTH) WISATA ALAM KALIWUNGU MELALUI PROGRAM PERHUTANAN SOSIAL OLEH DINAS KEHUTANAN PROVINSI JAWA BARAT - Aidah, Naila Ayu; ., Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The problem of the high number of people working in the agricultural sector (40,635,997 people) as well as the sector that has the highest percentage of poor households (51.33%) can be overcome by community empowerment through Social Forestry. Community empowerment of the Kaliwungu Nature Tourism Forest Farmer Group (KTH) through the Social Forestry Program by the West Java Provincial Forestry Service is an effort to improve community welfare through the use of access to state forest and land management in accordance with the principles of sustainability. This research aims to analyze the success of forest farmers group in West Java is being empowered through the Social Forestry Program and the factors that hinder the empowerment. The research method used is descriptive qualitative with data collection techniques. This research uses the theory of empowerment success expressed by Wrihatnolo and Dwijowijoto which can be seen through indicators of access, participation, control, and welfare. In identifying the factors inhibiting the implementation of empowerment, the theory expressed by Arsiyah is used. The results show that the access indicator is good, but participation, control, and welfare need more work. Community participation is still minimal, so participation is low. Control is not complete because most people only meet with administrators. Welfare cannot rely only on gardens and tourism. Factors that prevent empowerment include limited resources, management, marketing, and support from others. Suggestions include having online meetings, creating new tourist attractions, and teaching farmers management and marketing skills.